1998
DOI: 10.1088/0031-9155/43/12/019
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided analysis of conditions for optimizing practical electrorotation

Abstract: Previous studies have indicated that the variations in torque induced in particles in Electrorotation electrode arrays are sufficiently large to cause errors in electrorotation measurements. In order to avoid this, experimenters usually study particles bound by an arbitrary region near the centre of the electrodes. By simulating the time-dependent electric field for polynomial electrodes, we have assessed the variation in torque across the centre of the array. By considering both the variation in applied torqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…A common electrode configuration used in AC Electrokinetics research is a quadrupole arrangement where four electrodes point towards a central enclosed region [Huang and Pethig 1991], as shown in the schematic in figure 5. These electrodes may be of a variety of designs, according to the degree of field non-uniformity required [Hughes 1998]. The advantage with this arrangement is twofold.…”
Section: Electrode Configurationsmentioning
confidence: 99%
“…A common electrode configuration used in AC Electrokinetics research is a quadrupole arrangement where four electrodes point towards a central enclosed region [Huang and Pethig 1991], as shown in the schematic in figure 5. These electrodes may be of a variety of designs, according to the degree of field non-uniformity required [Hughes 1998]. The advantage with this arrangement is twofold.…”
Section: Electrode Configurationsmentioning
confidence: 99%
“…To generate the rotating field, the electrodes are driven by four sinusoidal voltages of equal amplitude V = 5 V successively phase-shifted by π/2 [13,39,40]. We study the frequency range from 10 kHz to 300 MHz and assume that the electrode response is linear, i.e., that no frequency components other than those applied to the electrodes can evolve in the chamber and that electrode polarization effects are negligibly small.…”
Section: A Electrorotation Chambermentioning
confidence: 99%
“…In Ref. [51] it is shown that the complex surface densityτ satisfies the integral equatioñ (13) whereτ 0 (r) = ε 0 E 0n (r), E 0n (r) is the normal component of the field produced by the external sources, and S is the interface. The generalization of Eq.…”
Section: Equivalent Permittivity and Second-order Contribution Fromentioning
confidence: 99%
See 1 more Smart Citation
“…When a cell is exposed to an electric field, a dipole is induced, whose character is dependent on the composition of the cell, the frequency of the applied electric field, and the conductivity of the medium in which the cell is suspended (107, 111, 131). In the presence of a rotating electric field, the dipole will form across the cell in synchrony with the rotation rate of the field (110). If the field is rotating with sufficiently high frequency, though, formation of the dipole may become asynchronous with the field's rotation rate.…”
Section: Vol 68 2004 Single-cell Microbiology 549mentioning
confidence: 99%